1998
DOI: 10.1074/jbc.273.47.31607
|View full text |Cite
|
Sign up to set email alerts
|

Mast Cell-/Basophil-specific Transcriptional Regulation of Human l-Histidine Decarboxylase Gene by CpG Methylation in the Promoter Region

Abstract: L-Histidine decarboxylase (HDC) catalyzes the formation of histamine from L-histidine, and in hematopoietic cell lineages the gene is expressed only in mast cells and basophils. We attempted here to discover how HDC gene expression is restricted in these cells. In the cultured cell lines tested, only the mast cells and basophils strongly transcribed the HDC gene. However, in transient transfection analysis, the reporter constructs with the HDC promoter were active not only in expressing cells but also in nonex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
41
0
2

Year Published

2001
2001
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(46 citation statements)
references
References 50 publications
3
41
0
2
Order By: Relevance
“…In addition, cis element modifications, such as DNA methylation, could also be important in regulating gene expression during growth and development [17±19]. DNA methylation was recently shown to contribute to the cell-specific expression of the gene encoding l-histidine decarboxylase and cyclin D1 [16,20]. We have also found that demethylation of specific CpG sites, as well as a methylation-sensitive transcription factor, contribute to the sex-specific expression of the Cyp2d-9 gene and to the cell-specific expression of the thyrotropin receptor gene [21,22].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, cis element modifications, such as DNA methylation, could also be important in regulating gene expression during growth and development [17±19]. DNA methylation was recently shown to contribute to the cell-specific expression of the gene encoding l-histidine decarboxylase and cyclin D1 [16,20]. We have also found that demethylation of specific CpG sites, as well as a methylation-sensitive transcription factor, contribute to the sex-specific expression of the Cyp2d-9 gene and to the cell-specific expression of the thyrotropin receptor gene [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…We also showed that the binding sites for Sp1 within the leptin gene promoter are located between nt ±115 and nt ±70. The in vitro binding of proteins to DNA does not always reflect binding in vivo [16,26]. Indeed, Sp1 can bind to a promoter and activate transcription in vitro even when the CpG site within the Sp1 binding site is methylated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggested that Sp1 might in part determine the tissue specificity of the mAbcc6 gene expression. Because tissue specificity can be determined by methylation at Sp1 sites, the binding of Sp1 transcription factor was suggested to protect the genomic DNA from being methylated [40] [41] [42] [43]. Aranyi et al [28] described the presence of a CpG island in the human proximal promoter and suggested that methylation at this site could influence the tissue specific gene expression of ABCC6.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, by using different protein kinase inhibitors, it has been shown that the mechanism of pituitary adenylate cyclase-activating polypeptide regulation is distinct from gastrin regulation of the HDC promoter (18). Interestingly, the DNA methylation state of the HDC promoter region has been also shown to control HDC gene expression in both the human and mouse (19,20). The HDC promoter region was demethylated in the HDC-expressing cell lines, such as the differentiated mast cell line MC9 and the erythroleukemia cell line DS19.…”
mentioning
confidence: 99%